Determination of the activation parameters ∆H≠ and ∆S≠ via a kinetic study of d, l-mandelic acid oxidation by using chromic acid in the presence of 1, 10-phenanthroline as a promoter in an aqueous micellar acid medium. Issue 11 (November 2021) - Islam, Monirul; Singha, Swarnava; Bhattacharyya, Anwesha; Roy, Debraj
Chromic acid oxidation ofd, l -mandelic acid in the presence and absence of 1, 10-phenanthroline (Phen) is studied in an aqueous micellar medium under kinetic conditions, [d, l -mandelic acid] >> [Phen]T >> [Cr(VI)]T at different temperatures. From studies on the effect of temperature on the rate constant (k), the activation parameters ∆H ≠ (enthalpy of activation) and ∆S ≠ (entropy of activation) are evaluated by using the Eyring equation [−ln (kh/kB T) = ∆H ≠ /RT − ∆S ≠ /R]. The high value of ∆H ≠ indicates that the phen-catalysed path is favoured mainly due to very high negative value of ∆S ≠ . The negative value of ∆S ≠ and the composite rate constant k cat support the suggested cyclic transition state. Both the catalysed and uncatalysed paths show a first-order dependence on [H + ], and both also show a first-order dependence on [d, l -mandelic acid]T and [Cr(VI)]T . The Phen-catalysed path is first order in [Phen]T . These observations remain unaltered in the presence of externally added surfactants. The cationic surfactant N -cetylpyridinium chloride is found to retard the rate of the reaction.